Good business practices improve productivity in Myanmar's manufacturing sector: Evidence from two matched employer-employee surveys - Paolo Falco; Henrik Hansen; John Rand; Finn Tarp; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We look into the relationship between business practices and enterprise productivity using panel data with matched employer and employee information from Myanmar. The data show that micro, small, and medium-size enterprises in Myanmar typically do only a few modern business practices. Even so, through estimates of value-added functions and labour demand relations we find a positive and economically important association between business practices and productivity. The results are confirmed when we utilize employer-employee information to estimate Mincer-type wage regressions. In combination, the value-added functions and the Mincer regressions show that at least half of the productivity gain from improved business practices stems from selection effects of employment of more productive workers. This sorting channel is important to keep in mind when supporting enterprises in Myanmar's manufacturing sector through entrepreneurial training activities. While our results indicate that implementation of more structured business practices could be a key ingredient of a private sector development strategy in Myanmar, the full effect of such a strategy may take time to materialize. Moreover, entrepreneurial training should be accompanied by labour market initiatives aimed at improving productive matches of employers and employees.
Keywords: D22; L2; M21; O53; 330; business practices; management; productivity; Myanmar